A behavioral approach to asset pricing - Shefrin, Hersh, 1948- (Academic Press advanced finance series., 2008)
Behavioral finance is the study of how psychology affects financial decision making and financial markets. It is increasingly becoming the common way of understanding investor behavior and stock market activity. In this 2nd Edition Hersh Shefrin examines the reigning assumptions of asset pricing theory and reconstructs them to incorporate findings from behavioral finance. In other words, he takes the traditional tools in asset pricing and behavioralizes them. He constructs a solid, intact structure that challenges classic assumptions and at the same time provides a strong theory and efficient empirical tools. Building on the models developed by both traditional asset pricing theorists and behavioral asset pricing theorists, Shefrin's book takes the discussion to the next step. He provides a general behaviorally based intertemporal treatment of asset pricing theory that extends to the discussion of derivatives, fixed income securities, mean-variance efficient portfolios, and the market portfolio, based on all the latest research and theory. * The second edition continues the tradition of the first edition by being the one and only book to focus completely on how behavioral finance principles affect asset pricing, now with its theory deepened and enriched by a plethora of research since the first edition * A companion website contains a series of examples worked out as Excel spreadsheets so that readers can input their own data to test the results.